Asuhan Keperawatan Jiwa Pada Pasien Dengan Halusnasi Pendengaran Di Ruang Melati Rsj Prof. Dr. Hb, Sa’anin Padang Tahun 2026 - Silvia Jelita; Dwi Happy Anggia Sari; Ramaita .; Vivi Yuderna (CV. ITTC INDONESIA, 2026)
Hallucinations are disturbances in sensory perception in which individuals experience false sensations such as hearing voices, seeing, tasting, touching, or smelling things that are not actually present. These disturbances can affect cognition, emotional control, and behavior, thereby influencing an individual’s functional abilities (American Psychiatric Association, 2022). The World Health Organization reported that approximately 970 million people worldwide experienced mental disorders in 2023, increasing to more than 1.1 billion people in 2024. In Indonesia, mental health remains a significant concern, with a prevalence of 1.3% in West Sumatra Province (Indonesia Health Survey, 2023). The Prof. HB. Saanin Mental Hospital in Padang is recorded as the hospital with the highest number of psychiatric patient visits in the region, reaching 38,332 visits in 2024 and remaining high in 2025. This study aims to describe psychiatric nursing care for patients with auditory hallucinations in Wisma Melati at Prof. HB. Saanin Mental Hospital, Padang, in 2026. Nursing care was provided through theimplementation of the Implementation Strategy (SP), which includes practicing rebuking the hallucinations, medication adherence, engaging in conversations, and performing scheduled activities. The five-day implementation showed an improvement in the patient’s ability to control auditory hallucinations. The results of this study emphasize the importance of the nurse’s role in providing comprehensive psychiatric nursing care to help patients control violent behavior and prevent risks to themselves and their environment.